A serine/threonine kinase gene defective in Peutz-Jeghers syndrome. - Hemminki, A; Markie, D; Tomlinson, I; Avizienyte, E; Roth, S; Loukola, A; Bignell, G; Warren, W; Aminoff, M; Höglund, P; Järvinen, H; Kristo, P; et al. (1998)
Studies of hereditary cancer syndromes have contributed greatly to our understanding of molecular events involved in tumorigenesis. Here we investigate the molecular background of the Peutz-Jeghers syndrome (PJS), a rare hereditary disease in which there is predisposition to benign and malignant tumours of many organ systems. A locus for this condition was recently assigned to chromosome 19p. We have identified truncating germline mutations in a gene residing on chromosome 19p in multiple individuals affected by PJS. This previously identified but unmapped gene, LKB1, has strong homology to a cytoplasmic Xenopus serine/threonine protein kinase XEEK1, and weaker similarity to many other protein kinases. Peutz-Jeghers syndrome is therefore the first cancer-susceptibility syndrome to be identified that is due to inactivating mutations in a protein kinase.